Management of School Partnership Program with Business World in Vocational High Schools: A Multi-Site Study - Arifin, Samsul; Roesminingsih, Erny; Riyanto, Yatim; Khamidi, Amrozi; Nursalim, Mochamad (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe and analyze the management of partnership programs between Vocational High Schools and the Business World and Industry through a multi-site study approach at SMKN 1 Driyorejo and SMKN 1 Duduksampeyan. The focus of the study includes planning, organizing, implementing, and evaluating partnership programs carried out by both schools in order to improve student competency. This study uses a qualitative approach with a multi-site study design and data collection techniques in the form of in-depth interviews, participatory observation, and documentation. The results of the study indicate that SMKN 1 Driyorejo is superior in implementing Teaching Factory which directly involves industry in learning, while SMKN 1 Duduksampeyan tends to implement partnerships in the form of Field Work Practices, industrial visits, and guest teachers. Both schools have established productive partnerships with the industrial world, but there are challenges such as the imbalance of partners between expertise competencies, limited practice facilities, and the need for a standardized evaluation system. Cross-site analysis revealed that partnership success is strongly influenced by strategic planning, collaborative organizing, real-world production-based implementation, and industry-involved evaluation. It is recommended that schools strengthen partnership management structures, businesses and industries expand their roles in vocational education, governments provide standard regulations and incentives, and higher education institutions develop replication models and further research. These findings are expected to be a strategic model in strengthening partnership-based vocational education in Indonesia.